Implementing human factors in anaesthesia: guidance for clinicians, departments and hospitals: Guidelines from the Difficult Airway Society and the Association of Anaesthetists. (11th January 2023) - Kelly, F. E.; Frerk, C.; Bailey, C. R.; Cook, T. M.; Ferguson, K.; Flin, R.; Fong, K.; Groom, P.; John, C.; Lang, A. R.; Meek, T.; Miller, K. L.; et al.
Summary: Human factors is an evidence‐based scientific discipline used in safety critical industries to improve safety and worker well‐being. The implementation of human factors strategies in anaesthesia has the potential to reduce the reliance on exceptional personal and team performance to provide safe and high‐quality patient care. To encourage the adoption of human factors science in anaesthesia, the Difficult Airway Society and the Association of Anaesthetists established a Working Party, including anaesthetists and operating theatre team members with human factors expertise and/or interest, plus a human factors scientist, an industrial psychologist and an experimental psychologist/implementation scientist. A three‐stage Delphi process was used to formulate a set of 12 recommendations: these are described using a 'hierarchy of controls' model and classified into design, barriers, mitigations and education and training strategies. Although most anaesthetic knowledge of human factors concerns non‐technical skills, such as teamwork and communication, human factors is a broad‐based scientific discipline with many other additional aspects that are just as important. Indeed, the human factors strategies most likely to have the greatest impact are those related to the design of safe working environments, equipment and systems. While our recommendations are primarily provided for anaesthetists and the teams they work with, there are likely to be lessons for others working in healthcare beyond the speciality of anaesthesia.